Subwavelength Diffractive Optical Elements for Generation of Terahertz Coherent Beams with Pre-Given Polarization State - Vladimir Pavelyev; Svetlana Khonina; Sergey Degtyarev; Konstantin Tukmakov; Anton Reshetnikov; Vasily Gerasimov; Natalya Osintseva; Boris Knyazev (Sensors, 2023)
Coherent terahertz beams with radial polarization of the 1st, 2nd, and 3rd orders have been generated with the use of silicon subwavelength diffractive optical elements (DOEs). Silicon elements were fabricated by a technology similar to the technology used before for the fabrication of DOEs forming laser terahertz beams with pre-given mode content. The beam of the terahertz Novosibirsk Free Electron Laser was used as the illuminating beam. The experimental results are in good agreement with the results of the computer simulation.